Letter (copy) - Citrine, Walter, 1887-1983
013-0040-001 Secretary's WMC/FEM/KA/392 PERSONAL 28th February 1941 Mr. L. Araquistain, 113 Arthur Court, Queensway, W.2. Dear Mr. Araquistain, Thank you for your letter of the 26th February. I was very glad to hear that all Spaniards arrested in unoccupied France after the demand of extradition by General Franco are now free again, except our mutual friend Caballero. I have, of course, been very anxious indeed about his fate. When I was in the States this question was taken up with Mr. Green of the American Federation of Labor, and it was very strongly urged that they should do all they can to help our old friend Francisco Caballero. Yours sincerely, General Secretary 292/946/13/40